The cost of remoteness revisited - Richard Franke (Kiel Institute for the World Economy (IfW), 2017)
Redding and Sturm (2008) use the German division as a natural experiment to study the importance of market access for regional development. They show empirically that cities close to the East-West German border experienced a significant decline in population growth due to division. I argue that their results are driven by the internal migration of refugees in the 1950s rather than the loss of market access. In fact, the treatment effect estimated by Redding and Sturm (2008) disappears completely once the refugee share in 1950 and boundary changes of sample cities are taken into account.
Keywords: F15; N94; R12; R23; 330; Market Access; Regional Growth; Internal Migration